CAR-based immunotherapy for breast cancer: peculiarities, ongoing investigations, and future strategies - Niu, Zhipu; Wu, Jingyuan; Zhao, Qiancheng; Zhang, Jinyu; Zhang, Pengyu; Yang, Yiming (Frontiers in Immunology, 2024)
Surgery, chemotherapy, and endocrine therapy have improved the overall survival and postoperative recurrence rates of Luminal A, Luminal B, and HER2-positive breast cancers but treatment modalities for triple-negative breast cancer (TNBC) with poor prognosis remain limited. The effective application of the rapidly developing chimeric antigen receptor (CAR)-T cell therapy in hematological tumors provides new ideas for the treatment of breast cancer. Choosing suitable and specific targets is crucial for applying CAR-T therapy for breast cancer treatment. In this paper, we summarize CAR-T therapy's effective targets and potential targets in different subtypes based on the existing research progress, especially for TNBC. CAR-based immunotherapy has resulted in advancements in the treatment of breast cancer. CAR-macrophages, CAR-NK cells, and CAR-mesenchymal stem cells (MSCs) may be more effective and safer for treating solid tumors, such as breast cancer. However, the tumor microenvironment (TME) of breast tumors and the side effects of CAR-T therapy pose challenges to CAR-based immunotherapy. CAR-T cells and CAR-NK cells-derived exosomes are advantageous in tumor therapy. Exosomes carrying CAR for breast cancer immunotherapy are of immense research value and may provide a treatment modality with good treatment effects. In this review, we provide an overview of the development and challenges of CAR-based immunotherapy in treating different subtypes of breast cancer and discuss the progress of CAR-expressing exosomes for breast cancer treatment. We elaborate on the development of CAR-T cells in TNBC therapy and the prospects of using CAR-macrophages, CAR-NK cells, and CAR-MSCs for treating breast cancer.